Magnetoelastic coupling and possibility of spintronic electromagnetomechanical effects: Магнетизм - Gomonay, Helen V.; Kondovych, Svitlana V.; Loktev, Vadim M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Nanoelectromagnetomechanical systems (NEMMS) open up a new path for the development of high speed autonomous nanoresonators and signal generators that could be used as actuators, for information processing, as elements of quantum computers etc. Those NEMMS that include ferromagnetic layers could be controlled by the electric current due to effects related with spin transfer. In the present paper we discuss another situation when the current-controlled behavior of nanorod that includes an antiferro- (instead of one of ferro-) magnetic layer. We argue that in this case ac spin-polarized current can also induce resonant coupled magnetomechanical oscillations and produce an oscillating magnetization of antiferromagnetic (AFM) layer. These effects are caused by i) spin-transfer torque exerted to AFM at the interface with nonmagnetic spacer and by ii) the effective magnetic field produced by the spin-polarized free electrons due to sd-exchange. The described nanorod with an AFM layer can find an application in magnetometry and as a current-controlled high-frequency mechanical oscillator.